Relationship between Pre-Pregnancy Body Mass Index and Childbirth Outcomes in Primiparous Women - Dadras; Ahmadi; Danesh-Kojuri; Hosseini (Iran University of Medical Sciences, 2010)
Background and Aim: Pregnancy is a physiological event that may cause significant complications (5-20%) in mother and fetus. One of the dangerous factors in the pregnancy is abnormal Body Mass Index (BMI) before pregnancy. The purpose of this study was to determine the relationship between maternal pre-pregnancy body mass index and childbirth outcomes in primiparous women.   Material and Method: This was a correlation and Ex-post facto study. Through consecutive sampling method, 300 primiparous women with the singleton pregnancy who received prenatal care in the first trimester (14 weeks) were selected. A record sheet (questionnaire) was used to collect data.   Result: The findings showed that there was a statistically significant relationship between body mass index and duration of first (P=0.007) and second stage of labor (P=0.01). Besides, increase in the body mass index was correlated with higher in cesarean rate. So, statistically significant relationship were found between body mass index and mode of delivery (P=0.03). However, no statistical significant relationship was found between body mass index and postpartum hemorrhage.   Conclusion: According to the finding, it seems that it would be necessary to plan educational and counseling programs before the pregnancy for the mothers.